The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.3389/fmolb.2021.655549
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effect of Chlorogenic Acid and Its Analogues on Lead-Induced Developmental Neurotoxicity Through Modulating Oxidative Stress and Autophagy

Abstract: Lead (Pb) is among the deleterious heavy metal and has caused global health concerns due to its tendency to cause a detrimental effect on the development of the central nervous system (CNS). Despite being a serious health concern, treatment of Pb poisoning is not yet available, reflecting the pressing need for compounds that can relieve Pb-induced toxicity, especially neurotoxicity. In the quest of exploring protective strategies against Pb-induced developmental neurotoxicity, compounds from natural resources … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 65 publications
1
17
0
Order By: Relevance
“…However, we noted that dietary supplementation of CGA induced autophagy in oxidatively stressed broilers, as evidenced by the increased LC3-II, Beclin1 and ATG7 mRNA expressions and LC3-II/LC3-I value and decreased mRNA expression of LC3-I and protein expression of p62, implying CGA inhibits oxidative stress through the activation of autophagy. Similar results were found in human neuroblastoma cells ( Gao et al, 2021 ) and zebrafish ( Ji et al, 2021 ). Moreover, with regards to apoptosis, our results showed that dietary supplementation of CGA decreased the mRNA expression of Caspase-9 in oxidatively stressed broilers, which was consistent with a previous study ( Liu et al, 2020 ) that found CGA inhibited the expressions of apoptosis-related proteins (caspase-3 and caspase-9) in the ischemia/reperfusion injury of rats.…”
Section: Discussionsupporting
confidence: 85%
“…However, we noted that dietary supplementation of CGA induced autophagy in oxidatively stressed broilers, as evidenced by the increased LC3-II, Beclin1 and ATG7 mRNA expressions and LC3-II/LC3-I value and decreased mRNA expression of LC3-I and protein expression of p62, implying CGA inhibits oxidative stress through the activation of autophagy. Similar results were found in human neuroblastoma cells ( Gao et al, 2021 ) and zebrafish ( Ji et al, 2021 ). Moreover, with regards to apoptosis, our results showed that dietary supplementation of CGA decreased the mRNA expression of Caspase-9 in oxidatively stressed broilers, which was consistent with a previous study ( Liu et al, 2020 ) that found CGA inhibited the expressions of apoptosis-related proteins (caspase-3 and caspase-9) in the ischemia/reperfusion injury of rats.…”
Section: Discussionsupporting
confidence: 85%
“…for 8 weeks) decreased hepato‐renal damage induced by Pb (1.34 g/L in drinking water) in mice by restoration of Pb‐suppressed activities of GSH, SOD, CAT, and GPx and diminishing Pb‐induced MDA levels (Cheng, Li, et al, 2019). In addition, the neuroprotective activity of CGA (100 μM) against Pb (1000 μg/L) in zebrafish larvae was attributed to the suppression of oxidative stress (Ji et al, 2021).…”
Section: Metalsmentioning
confidence: 99%
“…First, the results of this study need to be further validated, especially in AD transgenic animal models and related cell models. Second, we also found that RO5-violating CR phytochemicals (chlorogenic acid, cryptochlorogenic acid, and 3,5-O-dicaffeoylquinic acid) have some neuroprotective effects ( Kwon et al, 2010 ; Heitman and Ingram, 2017 ; Ji et al, 2021 ). This suggested that overemphasizing RO5 has the dangerous potential to overfilter compounds that may otherwise be good drug candidates and this inevitably results in reduced productivity for discovering new drugs.…”
Section: Discussionmentioning
confidence: 65%